ETHNOPEDAGOGY FOR EARLY CHILDHOOD IN THE OSING TRIBE BANYUWANGI REGENCY - Andini, Yuli Tri; Atika, Aisyah Nur; Tanto, Oktavian Dwi; Saputri, Senny Weyara Dienda (PG PAUD Universitas Negeri Surabaya, 2024)
The introduction of learning through local culture is one of the efforts to preserve indigenous cultures, enabling children to experience and participate in activities related to local traditions. Cultural activities contain unique values that can be used as learning tools in schools, both as an introduction and as a habitual practice. Banyuwangi Regency, located in the easternmost part of East Java Province, remains strongly committed to preserving its indigenous cultural heritage, particularly the culture of the Osing Tribe. The Osing Tribe in Banyuwangi has numerous cultural activities that can be integrated into early childhood education, as children actively participate in various cultural events within their community. The purpose of this study is to explore the ethnopedagogy practices among the Osing Tribe in Banyuwangi, specifically in early childhood education. A qualitative descriptive ethnograpy method was used to observe and understand ethnopedagogy in the learning environment of Kartini Kindergarten in Kemiren Village, Banyuwangi. The study found that there are several learning activities at Kartini Kindergarten that incorporate Osing culture into the education and habituation processes, allowing children to internalize the cultural values of the Osing Tribe. These activities include wearing traditional attire as school uniforms, participating in Banyuwangi traditional dance extracurriculars, dedicating a special day each week to introduce Osing culture through typical Banyuwangi foods, using the Osing language in learning, and engaging in traditional games.